Preparation of Authentic Deed of Distribution of Land Rights by Notary - Nabila Tasya Ramadintya; Siti Malikhatun Badriyah (Badan Penerbit STIEPARI Press, 2025)
The making of a certificate of inheritance is carried out by a different official, which is based on the population group, there are three officials who are authorized to make a certificate of inheritance, namely the Notary, the Heritage Hall (BHP), or made by the heirs themselves on paper witnessed by the Head of Village / Village Head and strengthened by the Camat. This writing aims to analyze the process of making authentic deeds of inheritance distribution of land rights, the obstacles faced by the notary in making authentic deeds of inheritance distribution of land rights and their solutions. Based on the problems raised, the researcher used a legal research method with a normative juridical approach, namely using the positivist legis concept. Writing specifications use descriptive analytical. The data source comes from secondary data. This writing is analyzed qualitatively using the analysis knife of Islamic justice theory, legal certainty theory, and inheritance distribution theory. The results showed that: 1) the process of making the deed of inheritance distribution begins with the creation of a Certificate of Inheritance (SKW) is the first step in carrying out the process of distributing inheritance rights to land in Jepara. The next steps are as follows: The parties (the heirs) together appear before the notary in the presence of 2 (two) witnesses. Both parties brought the files which were the formal and material conditions that had been determined. The notary checks the files. The notary before making the deed checks the files of certificates carried by both parties. The Land Deed Making Official (PPAT) makes a will or certificate of inheritance according to the wishes of the heir. The will shall be signed by the heir and the PPAT (made in two copies). Making the deed of inheritance distribution must be done before the PPAT and witnessed by 2 (two) witnesses. 2) Constraints for the Maker of Land Deeds in the process of distributing inheritance of land rights, namely: legal substance constraints, legal structure constraints, and legal culture constraints. The solution to the obstacles faced by notaries, namely: Consulting and asking for help from government officials in the local village or sub-district, the government needs to disseminate information to the community. Provide information regarding the procedure and procedures for registration as well as incomplete documents to the applicant.